SELECTED THEMES IN ‘AL-NASIHATU AL-KUBRA’ AND ITS RELEVANCE TO THE PRINCIPLE OF SADD AL-DHARI’A - Shettima Abubakar (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
The introductory part of the theme started with a major jurisprudential ordinance of prohibition (al-Tahrim) of homicide. This indeed, has a direct bearing with the issue of ideological crises. The Islamic panel system is aimed at discouraging and protecting the entire society from criminal activities and crises that may occur and disrupt the peaceful coexistence of the people. In fact, this is why the Islamic panel system is universal system that suits all time and place. Therefore, this study is aimed at examining the potentialities of Principles of Fiqh in the selected themes as well as to determine the challenges of ideological calamities. The method used to gather the information was qualitative research method that involved desk research. The paper explored the potentialities of Fiqh Principles on the basis of the current Persisting Ideological Crises (P.I.C) that resulted to anarchy in Nigeria. This offered a great insight to the topical issues therein. It was also revealed that the themes were developed based on the principle of Sadd al-Dhari’a. The paper adopted desk review and secondary data for the research. Bagian pendahuluan dari tema dimulai dengan ordonansi yurisprudensi utama tentang larangan (al-Tahrim) pembunuhan. Hal ini memang berkaitan langsung dengan persoalan krisis ideologi. Sistem panel Islam bertujuan untuk mencegah dan melindungi seluruh masyarakat dari kegiatan kriminal dan krisis yang mungkin terjadi dan mengganggu koeksistensi damai umat. Padahal, inilah mengapa sistem panel Islam merupakan sistem universal yang sesuai dengan segala waktu dan tempat. Oleh karena itu, penelitian ini bertujuan untuk mengkaji potensi Prinsip-prinsip Fiqh dalam tema-tema terpilih serta untuk menentukan tantangan bencana ideologis. Metode yang digunakan untuk mengumpulkan informasi adalah metode penelitian kualitatif yang melibatkan desk research. Makalah ini mengeksplorasi potensi Prinsip Fiqh berdasarkan Krisis Ideologi Persisting (P.I.C) saat ini yang mengakibatkan anarki di Nigeria. Ini menawarkan wawasan yang bagus untuk isu-isu topikal di dalamnya. Diungkapkan pula bahwa tema-tema tersebut dikembangkan berdasarkan prinsip Sadd al-Dhari’a. Makalah ini mengadopsi tinjauan meja dan data sekunder untuk penelitian.